Analisis Kebijakan Pemerintah Dalam Perlindungan Orangutan Di Provinsi Kalimantan Timur: Analysis Of Government Policies For The Protection Of Orangutan In East Kalimantan Province - Yusuf, Muhamad (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2023)
The protection and management of conservation, biodiversity and ecosystems in Indonesia is essential, including the protection of endangered species. One of the endangered animals is the orangutan on the island of Borneo. In addition to the crushed, the orangutan population has also continued to decline due to poaching that has been rife over the past few decades. The area of natural forests from Indonesia is currently shrinking rapidly. So now animal life is increasingly threatened due to the rapid development of humans and increasingly sophisticated human civilization. The purpose of writing this article is to analyze the efforts made by the government in implementing policies in the protection of Bornean Orangutans. This research uses qualitative methods with a literature review approach. The results showed that the implementation of government policies in an effort to protect orangutans in Kalimantan is by conserving orangutans. However, in reality, conservation efforts often collide with various interests. Inhibiting policy implementation are the expansion of industrial estates and the conversion of forested areas that squeeze vast areas of orangutan habitat.